The winner’s curse? Temporal and spatial impacts of higher education expansion on graduate employment and social mobility - Yang, Po (Studies in Higher Education, 2023)
The massification of higher education has dramatically changed the association between credentials and jobs in advanced countries, while its impacts in transitional economies have received less academic attention. To address this research lacuna, the paper utilizes rich information from China’s national surveys of college graduates from 2003 to 2019 and multiple waves of census data to explore the temporal and spatial effects of tertiary education expansion on college graduates’ job sorting. Regression results from the fixed effects model and the two-stage least-squares model indicate that, on the temporal dimension, the higher education expansion has weakened ties between college credentials and quality jobs over the past 20 years. Recent graduates are more likely to work in informal, non-urban, and non-public sectors, and the college earnings premium has also declined. There is a persistent gap in employment outcomes between bachelor’s and associate degree holders. On the spatial dimension, the growing enrolment size leads to skill sorting towards low skilled regions. The study argues that the dynamic effects of college credentials may be explained by labour market flexibility and cohort crowding after higher education expansion. This paper calls for a critical reflection on the merit of further massification of higher education in developing economies, regarding its potential impacts on intergenerational inequality and regional inequality.